Chemical and Microbiological Studies of the Middle Salt Lagoon, Barrow, Alaska. - Boyd,William L.; Boyd,Josephine W. (1974)
The Mddle Salt Lagoon, adjacent to the Chukchi Sea, at Barrow, Alaska, is the depository for sewage from the Naval Arctic Research Laboratory. It is covered with ice for most of the year (9-10 months), and during 1972 the salinity reached a maximum of 106.50 degrees/00; concentration of other solutes and solids was also accompanied by ice growth. Minimum temperatures were -5C, the lowest of any of the coastal bodies of water in the vicinity. During the period of ice-cover, microbial populations were of a low order. During the summer when free-water was present, increases in numbers were observed particularly among marine and halophilic bacteria. Enteric indicator organisms for the most part were low, except at the sewage outfall and in bottom sediments. Although the lagoon, interacting with the nearby Sea, would appear to be an ideal, two-cell, sewage disposal system, very little of the sludge and other material concentrated near the bottom by ice growth found their way for dilution into the Sea.